2013
DOI: 10.1111/ijs.12197
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Paracrine Factors on the Survival of Cells of the Neurovascular Unit during Oxygen Glucose Deprivation

Abstract: Microglia-derived signaling molecules, but not angiogenic factors, were protective for neurovascular unit cells during oxygen glucose deprivation. This finding could identify a potential therapeutic target for ischemic stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 27 publications
1
23
1
Order By: Relevance
“…All our data points to the fact that endothelial cells experience O 2 and glucose deprivation more severely than the other cell types and show a higher susceptibility. Two publications by Ceruti et al and Redzic et al recently compared survival of primary rat ECs, ACs and PCs under OGD (0% O 2 ) conditions and similarly concluded that ECs are more susceptible than ACs and PCs [ 36 , 37 ]. Importantly, our data further suggests that ACs tolerate ischemic injury better than PCs.…”
Section: Discussionmentioning
confidence: 99%
“…All our data points to the fact that endothelial cells experience O 2 and glucose deprivation more severely than the other cell types and show a higher susceptibility. Two publications by Ceruti et al and Redzic et al recently compared survival of primary rat ECs, ACs and PCs under OGD (0% O 2 ) conditions and similarly concluded that ECs are more susceptible than ACs and PCs [ 36 , 37 ]. Importantly, our data further suggests that ACs tolerate ischemic injury better than PCs.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, vascular endothelial growth factor (VEGF) could be one major factor for BBB breakdown in our model. It was shown that VEGF was significantly upregulated in astrocytes after OGD or hypoxia, and it was postulated that this is responsible for BBB damage (Redzic et al, 2013 ). With regard to our model, C6 cells secreted significant amounts of VEGF which was further upregulated via hypoxia (Boveri et al, 2005 ; Yeh et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…How these die in stroke, and how this damage leads to dysfunction and partial recovery is less clear. In vitro data indicate that neurons are the most sensitive to oxygen/glucose deprivation, followed by endothelial cells, astrocytes, and microglia [8]. As with neurons, glutamate signaling may play a role in oligodendrocyte cell death after stroke, through both N-methyl-D-aspartate and α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid subtypes of the glutamate receptor [9].…”
Section: The Infarct Corementioning
confidence: 99%
“…In rodent stroke models, oligodendrocytes survive longer than neurons [10]. Astrocytes die at a somewhat later period in the same ischemic stimulus than neurons [8,11], and do so through mechanisms that involve swelling, adenosine triphosphate release and signaling through adenosine triphosphate receptors (P2Y 1 purinergic receptors [12]). With this differential sensitivity in mind, even in the short term in vivo, hours after the infarct, all cell types in the stroke core die.…”
Section: The Infarct Corementioning
confidence: 99%